CAUSES AND CHARACTERISTICS OF BUSINESS CYCLE IN LITHUANIA: A STRUCTURAL VARAPPROACH - Proškutė, Aurelija (Ekonomika, 2012)
We investigate the structural disturbances underlying the business cycle in Lithuania in the bivariate time series framework. In the structural VAR model constructed productivity, hours of work and output fluctuations over the business cycle are composed of technology and non-technology shocks. We find that a technology shock has a persistent positive effect on all three variables. Non-technology disturbance has a long-term impact on working hours and output, but it has a negligible short-run effect on productivity.Differently from Gali (1999), the study has revealed no significant correlation between productivity and working hours under the effects of technology shocks on Lithuanian data. In contrast with the results of developed countries, non-technology shocks result in a significant negative correlation between the working hours and labour productivity in Lithuania.Historical decomposition of output, productivity and working hours series allows distinguishing four different episodes of Lithuanian economy during the analysed timeline. In 1999, negative technology shocks played the biggest role in pushing the output down. During the period 2001–2004, the real GDP growth was supported by productivity increase due to technology shocks; in 2005–2008, non-technology shocks and the higher working hours were fuelling output growth together with a positive impact of the technology shock on productivity growth. Finally, 2008–2011 is the period of negative technology and non-technology shocks.